Estudio de factibilidad para la creación de una empresa productora y comercializadora de almuerzos saludables para organizaciones ubicadas en Cota (2019)
In this degree work a feasibility study was carried out for the creation of a company that produces and commercializes healthy lunches for organizations located in Cota through the tools and methodologies acquired during the industrial engineering career, complying with the thematic design proposed with the development and analysis of the diagnosis in the municipality of Cota and the sector and the food subsector and sale to the table of prepared meals, the objective of the market study was to identify the demand, potential customers and identify new market niches, the technical study to see the internal and productive operation of the business plan, the administrative study, strategic planning focused on fulfilling the vision of the organization, the environmental study strategies to improve and / or mitigate the impacts produced, the legal study to determine the aspects required in the constitution of the organization and finally the financial study to determine the viability and profitability of the Project.